2017
DOI: 10.1371/journal.pone.0177397
|View full text |Cite
|
Sign up to set email alerts
|

Differences of microparticle patterns between sickle cell anemia and hemoglobin SC patients

Abstract: Sickle cell anemia (SCA) and hemoglobin SC (HbSC) disease are the two most common forms of sickle cell disease (SCD), a frequent hemoglobinopathy which exhibits a highly variable clinical course. Although high levels of microparticles (MPs) have been consistently reported in SCA and evidence of their harmful impact on the SCA complication occurrences have been provided, no data on MP pattern in HbSC patients has been reported so far. In this study, we determined and compared the MP patterns of 84 HbSC and 96 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 54 publications
2
19
2
Order By: Relevance
“…Some studies identified further increases in the levels of RBCEVs in SCA patients during crisis compared to SCA patients at steady state [ 149 , 151 , 152 , 153 ]. However, complicating interpretation of data some studies have identified no significant differences in EV generation in SCA [ 145 , 146 ], while other experimental findings suggest increased levels of platelet-derived microparticles compared to RBCEVs in SCA [ 146 , 147 , 148 , 150 , 151 , 153 , 154 , 155 ]. Research efforts have attempted to assess RBCEVs in SCA patients to categorize non-severe and severe vaso-occlusive crises based on their circulating levels [ 150 ].…”
Section: Biological Roles Of Rbcevsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies identified further increases in the levels of RBCEVs in SCA patients during crisis compared to SCA patients at steady state [ 149 , 151 , 152 , 153 ]. However, complicating interpretation of data some studies have identified no significant differences in EV generation in SCA [ 145 , 146 ], while other experimental findings suggest increased levels of platelet-derived microparticles compared to RBCEVs in SCA [ 146 , 147 , 148 , 150 , 151 , 153 , 154 , 155 ]. Research efforts have attempted to assess RBCEVs in SCA patients to categorize non-severe and severe vaso-occlusive crises based on their circulating levels [ 150 ].…”
Section: Biological Roles Of Rbcevsmentioning
confidence: 99%
“…Research efforts have attempted to assess RBCEVs in SCA patients to categorize non-severe and severe vaso-occlusive crises based on their circulating levels [ 150 ]. Further, comparison of circulating EVs between SCA and Hb SC (HbSC) genotype patients identified significantly higher levels of total microparticles including both RBC- and platelet-derived EVs in SC compared to HbSC patients [ 155 ].…”
Section: Biological Roles Of Rbcevsmentioning
confidence: 99%
“…We included 232 adults with the SS phenotype in Bamako (n = 106) and Dakar (n = 126). Patients were within the same range of age [median (interquartile range, IQR) age of 26 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and 23 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years respectively]. These 232 patients were recalled for a specific visit at steady state in parallel in the two centres.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…43 Platelet function is significantly altered in SCD and is associated with an abnormal phenotype marked by surface-mobilized, activation-dependent antigens and microparticle formation. 44 Increased circulating activated platelets have been observed in patients with SCD 45 along with increased circulating levels of platelet products, such as thrombospondin and increased expression of P-selectin (which mediates the adhesion of erythrocytes and leukocytes in venules of sickle cell (b S ) transgenic mice). 43,46 In addition, evidence exists in patients with SCD of ongoing generation of thrombin, 47 which may mediate the platelet activation observed in this disease.…”
Section: Plateletsmentioning
confidence: 99%